Electrocatalysis and Determination of Ascorbic Acid Through Graphite Paste Electrode Modified With Iron Nitroprusside - Carmo,Devaney R. do (2004)
Iron nitroprusside, Fe(II)NP was incorporated into a carbon paste electrode and the electrochemical studies were performed by cyclic voltammetry. The cyclic voltammogram of the modified electrode, Fe(II)NP showed two redox couples ( E½ox)1 = 0.24 and (E½ox)2 = 0.85 V vs. SCE attributed to Fe(II)/Fe(III) and Fe(II)(CN)5NO / Fe(III)(CN)5NO, respectively. The redox couple at (E½ox)1 = 0.24 V presents an electrocatalytic response for ascorbic acid. The modified paste electrode exhibits a decrease of 180 mV in the ascorbic acid oxidation. The modified graphite paste electrode gives a linear range from 1.0 × 10-3 to 2.6 × 10-2 mol L-1 of ascorbic acid with a detection limit of 1.4 × 10-3 (±1.2%) mol L-1 (n =3). The electrocatalytic oxidation of ascorbic acid compounds by the mediator has been used for the determination of ascorbic acid in a commercially pharmaceutical available product.